Dosis de cerdaza y su efecto en las características agronómicas y rendimiento de forraje de Morus nigra "morera" en Zungarococha - 2021 - Perea Villacorta, Nucia Sly Yang (2022)
The use of the organic matter produced in the farms that are the manures is of great importance to be able to give them an advantage in the production of Pastures and forages and the National University of the Peruvian Amazon, has one of the Faculties that contributes research that is of Agronomy since it has a project that is for Cattle located in the Fundo de Zungarococha district of Belen, the present work is entitled DOSE OF CERDAZA AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS AND FORAGE YIELD OF Morus nigra "MORERA" IN ZUNGAROCOCHA - 2021. With a Complete Randomized Block Design (D.C.A), with four treatments and four repetitions, the treatments under study were: T0 (Control), T1 (10 ton/ha), T2 (20 ton/ha), T3 (30 ton /ha) obtaining the following results: With treatment T3 (30 ton/ha) it was possible to increase the yields of plant height (m), green matter (kg/m2), dry matter (kg/m2), number of leaves /plant (kg), number of repeated plants and green matter yield (kg/ha). In this sense, it was shown that at least one of the sow doses influenced plant height (m), green matter (kg/m2), green dry matter (kg/ha). According to what was found in this work, the dose of 30 ton/ha of sow has a positive influence on the research. (kg/m2), leaf/stem ratio (kg), number of repeated branches and material yield